Irrigation in Central Asia in figures : AQUASTAT survey - 2012 - Frenken, Karen (Water reports ;, 2013)
AQUASTAT, FAO's global information system on water and agriculture, was initiated by the Land and Water Division with a view to presenting a comprehensive picture of water resources and irrigation in the countries of Africa, Asia, Latin America and the Caribbean and providing systematic, up-to-date and reliable information on water for agriculture and rural development. This report presents the results of the most recent survey carried out in the six countries of the Central Asia region, and it analyses the changes that have occurred in the ten years since the first survey. Following the AQUASTAT methodology, the survey relied as much as possible on country-based statistics and information. The report consists of three sections. Section I describes in detail the methodology used and contains a glossary of the terms used. Section II contains the regional analysis presenting a synopsis on water resources, water use and irrigation in the region and the trends over the last ten years. It also describes the legislative and institutional framework for water management as well as environmental issues and it presents prospects for agricultural water management from the countries' perspective. Section III contains detailed country profiles for Afghanistan, Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan, and one river basin profile for the Aral Sea basin.